Computational analysis of the use of Twitter during the 2022 presidential debates in Costa Rica - Chavarría-Mora, Elías (2023)
In which ways did the conversation evolve around presidential candidates in 2022 in the social network Twitter during the presidential debates of Repretel and Teletica? In this exploratory research note, I use computational techniques such as dictionary analysis and unsupervised machine learning for topic modeling to explore this question, with the goal of adding to the growing number of quantitative research regarding social networks in Costa Rica. While the results are merely exploratory and do not test any hypothesis, they do not suggest a great presence of automated accounts during the debates. Rodrigo Chaves, as a topic, clearly dominated the conversation in Twitter, in particular with regards to the accusations of sexual harassment against him.